The Effect of RAP Strategy in Teaching Reading - Virgiyanti, Diska Fatima; Hafiz, Latifa Annisa (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
RAP (Read, Ask, and Put) is a strategy that instructs students to focus their reading on a particular section of the text, consider the main idea and supporting ideas of the paragraph or passage, and then explain it in their own words. This study aims to determine the achievement of fourth-year students at Gontor for girls 2nd campus in reading comprehension using the RAP strategy since the researchers found that their reading comprehension is still low. This research used a quantitative experimental method with an experimental non-equivalent control group design. The population in this study were all fourth-year students of Gontor for girls 2nd campus with 79 students and used probability sampling which is simple random sampling. The method used in data collection is the test method and is complemented by some documentation. For the data analysis, it used the formula SPSS 22. This study concluded that the use of the RAP strategy in teaching reading comprehension on reading subjects proved effective with the formula-test acquisition value of Sig.(2.tailed) 0.009 < 0.05. Based on the conclusion, the researcher provided suggestions, they are (1) the RAP Strategy is very likely to be used to teach the reading subject to students because the students try to think critically and will understand the text with comprehension; (2) it is hoped that teachers will develop and try to apply the RAP strategy in teaching reading. Thus, the students can independently find the main idea and use their prior knowledge of vocabulary